Development of Edutainment and Problem Solving Based Learning Comics to Enhance Elementary School Students’ Understanding of Magnet Concepts - ATIK KARLINA; Siska Desy Fatmaryanti; Nur Ngazizah (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aimed to design and develop a comic-based learning medium integrating edutainment and problem-solving approaches for teaching magnet concepts to fifth-grade elementary school students. The development process employed the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of 28 Grade 5 students at SD Negeri Sindurjan, five students involved in limited trials, and three expert validators (material, media, and instructional experts). Validation results showed that the developed comic achieved a highly valid category, with average scores exceeding 85 percent. Practicality testing through teacher and student responses also indicated very high practicality, with percentages above 90 percent, demonstrating that the comic is engaging, easy to use, and suitable for elementary learners. Effectiveness was evaluated through pretest and posttest comparisons, which revealed a substantial improvement in students’ understanding of magnet concepts, with high N-Gain values. The findings indicate that the developed comic effectively supports conceptual understanding, promotes active learning, and enhances students’ thinking skills. Therefore, the edutainment- and problem-solving-based comic is appropriate to be used as an innovative and interactive learning medium aligned with 21st-century learning principles